From Raffinose Family Oligosaccharides to Sucrose and Hexoses: Gene Expression Profiles Underlying Host-to-Nematode Carbon Delivery in Cucumis sativus Roots - Wang, Xingyi; Li, Shihui; Zhang, Xu; Gao, Lihong; Ruan, Yong-Ling; Tian, Yongqiang; Ma, Si (Frontiers in Plant Science, 2022)
Root-knot nematodes (Meloidogyne incognita) induce specific feeding sites in cucumber roots where they absorb carbon nutrients from the host, thereby turning the feeding sites into a strong sink for assimilates. Nematode infection may alter host sugar metabolism in the roots of sucrose-transporting species. However, much less is known about the species translocating raffinose family oligosaccharides (RFOs), such as cucumber. To address this knowledge gap, the dynamics of RFOs and sucrose metabolisms, two major sugar-metabolism processes, in cucumber roots during nematode infection at transcription and protein levels were analyzed. In the nematode-infected root, the expressions of RFO-synthesis genes, CsRS (Raffinose Synthase) and CsGolS1 (Galactinol Synthase 1), were upregulated at early stage, but were significantly decreased, along with CsSTS (Stachyose Synthase), at the late stage during nematode infection. By contrast, α-galactosidase hydrolyzed RFOs into sucrose and galactose, whose encoding genes was suppressed (CsaGA2) at early stage and then elevated (CsaGA2, 4, and CsAGA1) at the late stage of nematode infection. Consistently, stachyose level was significantly increased by ∼2.5 times at the early stage but reduced at the late stage of infection in comparison with the uninfected roots, with a similar trend found for raffinose and galactinol. Moreover, the genes encoding sucrose synthase and cell wall invertase, which are responsible for sucrose degrading, were differentially expressed. In addition, sugar transporter, CsSUT4, was enhanced significantly after nematode infection at early stage but was suppressed at the late stage. Based on the observation and in connection with the information from literature, the RFOs play a role in the protection of roots during the initial stage of infection but could be used by nematode as C nutrients at the late stage.